How Students' Use of E-Commerce, E-Money, Financial Literacy, Self-Control, and Lifestyle Affect Their Consumptive Behavior - Alzura, Daniza; Khalifaturofi'ah, Sholikha Oktavi (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
Consumptive behavior is the tendency to buy and use goods that are not based on rational considerations. This research aims to examine the influence of e-commerce, e-money, financial literacy, self-control, and lifestyle on the student's online shopping behavior located in the city of Surabaya, East Java. The sample used is 101 undergraduate or diploma students who live in Surabaya with a minimum allowance of IDR 2 million using a purposive sampling technique. The analysis technique used in the research is Partial Least Square (PLS) with the Structural Equation Model (SEM) method using WarpPLS 8.0 software. The results of this research find a mix of positive and negative impacts as well as significant and insignificant impacts from the variables used. This research provides an important contribution to understanding the dynamics of e-commerce, e-money, financial literacy, self-control, and lifestyle on the student's online shopping behavior especially located in the city of Surabaya, East Java.